Methamphetamine, 3, 4-methylenedioxymethamphetamine (MDMA) and 3, 4-methylenedioxypyrovalerone (MDPV) induce differential cytotoxic effects in bovine brain microvessel endothelial cells. (26th August 2016) - Rosas-Hernandez, Hector; Cuevas, Elvis; Lantz, Susan M.; Rice, Kenner C.; Gannon, Brenda M.; Fantegrossi, William E.; Gonzalez, Carmen; Paule, Merle G.; Ali, Syed F.
Abstract: Designer drugs such as synthetic psychostimulants are indicative of a worldwide problem of drug abuse and addiction. In addition to methamphetamine (METH), these drugs include 3, 4-methylenedioxy-methamphetamine (MDMA) and commercial preparations of synthetic cathinones including 3, 4-methylenedioxypyrovalerone (MDPV), typically referred to as "bath salts." These psychostimulants exert neurotoxic effects by altering monoamine systems in the brain. Additionally, METH and MDMA adversely affect the integrity of the blood-brain barrier (BBB): there are no current reports on the effects of MDPV on the BBB. The aim of this study was to compare the effects of METH, MDMA and MDPV on bovine brain microvessel endothelial cells (bBMVECs), an accepted in vitro model of the BBB. Confluent bBMVEC monolayers were treated with METH, MDMA and MDPV (0.5 mM–2.5 mM) for 24 h. METH and MDMA increased lactate dehydrogenase release only at the highest concentration (2.5 mM), whereas MDPV induced cytotoxicity at all concentrations. MDMA and METH decreased cellular proliferation only at 2.5 mM, with similar effects observed after MDPV exposures starting at 1 mM. Only MDPV increased reactive oxygen species production at all concentrations tested whereas all 3 drugs increased nitric oxide production. Morphological analysis revealed different patterns of compound-induced cell damage. METH induced vacuole formation at 1 mM and disruption of the monolayer at 2.5 mM. MDMA induced disruption of the endothelial monolayer from 1 mM without vacuolization. On the other hand, MDPV induced monolayer disruption at doses ≥0.5 mM without vacuole formation; at 2.5 mM, the few remaining cells lacked endothelial morphology. These data suggest that even though these synthetic psychostimulants alter monoaminergic systems, they each induce BBB toxicity by different mechanisms with MDPV being the most toxic.